(untitled) (International Current Pharmaceutical Journal, 2012)
Purification of the dichloromethane (CH2Cl2) fraction of the aqueous extract of Rubus suavissimus resulted in the isolation of two sterols namely stigmasterol and ?-sitosterol. The structures of the isolated compounds were characterized on the basis of extensive spectral data (1D and 2D NMR; and MS) and in comparison with their literature data. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11613 International Current Pharmaceutical Journal 2012, 1(9): 239-242